2006
DOI: 10.1176/appi.ajp.163.4.724
|View full text |Cite
|
Sign up to set email alerts
|

Patient Casemix Classification for Medicare Psychiatric Prospective Payment

Abstract: A regression model with 16 casemix groups restricted to using "appropriate" payment variables (i.e., those with clinical face validity and low administrative burden that are easily validated and provide proper care incentives) produced more efficient and equitable payments than did a noninteractive system based on diagnosis-related groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Six studies were conducted in multiple sites with large sample sizes (Group A) and two studies at a single site with smaller sample sizes (Group B). All studies in Group A were reported in multiple publications (Study 1: Cromwell et al 2004, 2005 a , b ; Cromwell & Maier, 2006; Drozd et al 2006; Study 2: Gaines et al 2003; Eagar et al 2004; Study 3: Hirdes et al 2002; Daniel, 2008; Study 4: Buckingham et al 1998 a , b ; Study 5: Yamauchi, 1997 a , b ; Study 6: Fries et al 1990, 1993). A total of 15 613 patient episodes were included with a range of 42–6554.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were conducted in multiple sites with large sample sizes (Group A) and two studies at a single site with smaller sample sizes (Group B). All studies in Group A were reported in multiple publications (Study 1: Cromwell et al 2004, 2005 a , b ; Cromwell & Maier, 2006; Drozd et al 2006; Study 2: Gaines et al 2003; Eagar et al 2004; Study 3: Hirdes et al 2002; Daniel, 2008; Study 4: Buckingham et al 1998 a , b ; Study 5: Yamauchi, 1997 a , b ; Study 6: Fries et al 1990, 1993). A total of 15 613 patient episodes were included with a range of 42–6554.…”
Section: Resultsmentioning
confidence: 99%
“…A razão apontada por Knapp e colaboradores [17] é que as taxas de reembolso nem sempre abrangem todos os custos associados às doenças mentais crónicas. A literatura sugere que o reembolso dos custos de saúde mental baseado num sistema de casemix deve considerar não só o tempo de internamento, mas também o diagnóstico, o grau de apoio social e de assistência nas atividades do dia-a-dia, a severidade da doença, se houve ou não referenciação pelo sistema judicial e a possibilidade de existir um comportamento “perigoso” [18]. Desta forma, Knapp e colaboradores [17] argumentam que nos países onde existam dados suficientes sobre a utilização dos recursos e custos, os GDHs, se bem construídos, podem apresentar-se como um modelo que assegura que recursos suficientes são transferidos para os cuidados secundários e especializados de saúde mental.…”
Section: Modalidades De Pagamento E Incentivos: Teoria E Resultadosunclassified
“…A further problem relevant to the discussion of the amount of explained variance is the relative invariance of the criteria variable treatment duration in our sample (variance coefficient of length of stay = 33%). Due to the fact that the length of stay is just a proxy for resource consumption, maybe the criteria variable “cost” used in the study of Drozd et al [6] is as close as possible to the actual intensity of care provided and is able to exhibit a higher explanation of variance. On the other hand, there is a lack of empirical data on the reliability and validity of the variable cost or per-diem costs.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, only a few studies have been conducted to develop and evaluate case group concepts for patients with mental disorders in different settings (outpatient, inpatient, and community mental health care) [1,4,5,6,9,11,12,15,18,21,22]. Some of these studies were conducted to refine the main diagnostic categories in the DRG system and they focused on analyses within specific diagnostic groups [1,6,9,15,18,19,21,22]. In contrast to these diagnosis-based approaches, we used an exploratory design by defining patient classes by different patient characteristics, in analogy to the studies of Buckingham et al [4] and Gaines et al [11].…”
Section: Introductionmentioning
confidence: 99%